Time-Optimal Control of Chemical Neutralization Process - Danilushkin, I.A.; Kolpashchikov, S.A.; Mandra, A.G. (2019 International Russian Automation Conference (RusAutoCon), 2019)
The existing heat and power generation technologies involve the utilization of chemically treated water. Water treatment produces alkaline and acidic wastewaters, which must be neutralized. The paper considers the problem of optimal control of the chemical neutralization of acidic wastewater by means of lime water. The installation for neutralization consists of a tank and a recycling pipeline. The mathematical model of chemical neutralization comprises systems of nonlinear differential equations in parabolic partial derivatives to take into account the chemical reaction between the interacting components placed in the recycling pipeline or in the tank. The controlling action is alkali inflow rate at the inlet of the recycling-pump. The optimization problem is formulated as a problem of time-optimal control. It is shown that the time-optimal process of chemical neutralization is also optimal from the point of view of the accuracy of approaching to the neutral state.